Giving Iron Tablets and Guava Juice Increases Hemoglobin Levels in STT Adolescent Girls in Tunjuk Village, Tabanan District - Ida Ayu Eka Padmiari; Ni Nengah Ariati; Pande Putu Sri Sugiani (CV. AFDIFAL MAJU BERKAH, 2026)
Based on 2018 Riskesdas data, the prevalence of anemia in adolescent girls is 26.8% with anemia sufferers aged 5-14 years. Prevention of anemia apart from giving blood supplement tablets, can be done with food interventions such as providing food sources of vitamin C. The aim of this research is to determine the effect of giving blood supplement tablets and giving red guava juice on increasing hemoglobin levels in young women at Tunjuk Village, Tabanan District. The type of research is a quasi-experiment with a two group pre-test and post-test design. Location at Tunjuk Village, Tabanan District in Juni October 2025. The research sample was STT Adolescent Girls in Tunjuk Village, Tabanan District. The independent variables of the research were consumption of blood supplement tablets and guava juice, while the dependent variable was the hemoglobin levels of young women.